The grip pressure analysis of three badminton forehand overhead strokes - a case study - Pan, K.-M.; Kao, F.; Tsai, C. L. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The purpose of this study was to analyze the palm distribution variables (finger forces and pressure) on the dominant hand of a collegiate 1st class female badminton player when performing drop, clear, and smash overhead strokes. We aimed to analyze from the preparation period to the contact point with the shuttle. A high-speed digital camera (2000Hz) and a grip measurement system (500Hz) were simultaneously used to record the 2D movement and collect 18 palm areas of grip force and pressure of the dominant hand. The results showed that the finger signal of the forehand overhead strokes of the participant was similar for both clear and smash strokes. The peak grip pressure of the movements appeared before the contact point in all three different overhead strokes. Based on the results, we suggest that increasing grip strength training might enhance shuttle velocity.